Universal mathematical model of power three-phase transformers and autotransformers; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Gusev A. S. Alexander Sergeevich (Power engineering, 2007)
Заглавие с титульного листа